Tuning of carrier type, enhancement of Linear magnetoresistance and inducing ferromagnetism at room temperature with Cu doping in Bi2Te3 Topological Insulators. (February 2018) - Singh, Abhishek; Singh, Rahul; Patel, T.; Okram, G.S.; Lakhani, A.; Ganeshan, V.; Ghosh, A.K.; Jha, S.N.; Patil, Swapnil; Chatterjee, Sandip
Graphical abstract: Clear observation of charge carrier tuning and large thermoelectric power factor. Highlights: With Cu doping in Bi2 Te3, resistivity increases as Fermi level is shifted into valence band with extra scattering centers. Cu doping tunes the carrier from n to p type, which is attributed to the presence of TeBi and BiTe antisites. The observed Linear Magneto resistance is believed to be associated with gapless linear energy spectrum of surface Dirac Fermions. Cu doping induces room temperature ferromagnetism. Abstract: Structural, resistivity, thermoelectric power, magneto-transport and magnetic properties of Cu doped Bi2 Te3 topological insulators have been investigated. The tuning of charge carriers from n to p type by Cu doping at Te sites of Bi2 Te3 is observed both from Hall effect and thermoelectric power measurements. Carrier mobility decreases with the doping of Cu which provides evidence of the movement of Fermi level from bulk conduction band to the bulk valence band. Thermoelectric power also increases with doping of Cu. Moreover, linear magnetoresistance (LMR) is observed at high magnetic field in pure Bi2 Te3 which is associated to the gapless topological surface states protected by time reversal symmetry (TRS). Furthermore, doping of non-magnetic Cu induces ferromagnetism at room temperature and also enhances the magnetoresistance.